Enhanced performance of alpha‐Fe2O3 nanoparticles with optimized graphene coated layer as anodes for lithium‐ion batteries. (26th July 2019) - Zhou, Fen; Zeng, Liuli; Guo, Wei; Yan, Yizhi; Wu, Fan; Pan, Mu
Summary: A series of different α‐Fe2 O3 nanoparticles composites containing different amounts of graphene coatings have been successfully prepared using a simple electrostatic self‐assembly (ESA) method. The structure and electrochemical properties of these α‐Fe2 O3 @graphene composites have been investigated. The α‐Fe2 O3 nanoparticles composite containing 40 wt% graphene coating exhibits the highest specific capacity (385 mAh g −1 ) under 1000 mA g −1, resulting in superior cycle stability with no downward trend after 500 cycles. These results demonstrate that graphene coatings can be used to enhance the electrochemical properties and morphological stability of α‐Fe2 O3 nanoparticles as anodic materials for high performance lithium‐ion batteries (LIBs). The low‐energy self‐assembly method employed in the paper has good potential for the broad‐scale preparation of other graphene‐modified materials because of its simplicity and the relatively low temperature conditions. Abstract :